An Evaluation on Deep Caries Removal Method and Management Performed by Undergraduate Dental Students: A Malaysia Experience - Othman, Nurin Izyani; Ismail, Hanan Umaira; Mohammad, Norazlina; Ghazali, Norzalina; Alauddin, Muhammad Syafiq (European Journal of Dentistry, 2020)
Objectives The aim of this study was to investigate the current knowledge and attitude of deep caries removal method among dental students in Malaysia.Materials and Methods A total of 303 students (n = 303) responded to the online questionnaire. The first part of questionnaire was to evaluate the demographic data of the respondents and focused on the technique and management approach used for deep caries lesion. The second part investigated the preferred treatment used for deep caries based on the designated clinical case, while the third part assessed the factors that affected the decision on deep caries management.Statistical Analysis Independent t-test was used to compare difference between the two groups.Results Seventy four percent of the students have the knowledge of the different methods of caries removal, while 25.8% were only familiar with complete caries removal. The preferred method for deep caries removal in permanent teeth was partial caries removal (53%). For primary dentition, 45.6% of the students prefer to perform pulpotomy as compared with other techniques. There was no significant difference in caries removal method for permanent teeth between undergraduate year of study (p > 0.05), which was partial caries removal at 52.7 and 53.5%, respectively. For primary dentition, the preferred caries removal method was pulpotomy for year 4 (39.8%) and year 5 (52%) students. The popular material to restore deep caries was resin composite (42%) followed by glass ionomer cement (23.3%).Conclusions This study showed that partial caries removal was the preferred method despite partial understanding on the identification of the clinical indicators of the technique.
Keywords: deep caries; complete removal caries; partial caries removal; dental education; pulpotomy; conservative dentistry